Commerce, corruption and control: Bolshevik approaches to trade, 1917-1923 - Nicholson, Joseph (2019)
This thesis studies the Bolshevik party's approaches to trade during the Russian revolution, civil war, and the early years of the New Economic Policy (1917-1923). It adopts three perspectives. One of these is theoretical. It covers the beliefs and stereotypes party members held about capitalist trade, the economic and social roles they attributed to it, and their visions of how goods would be exchanged under socialism. The thesis also considers policy approaches. It examines the steps the party leadership actually took after coming to power to try to shape the way goods were exchanged in the country, whether in a bid to put their theories into reality, or as practical responses to the challenges facing them at the time. Thirdly, the thesis analyses the approaches of party-state functionaries responsible for implementing these policies at ground level. It studies their attitudes towards the central leadership, the ways they understood its directives, and how they attempted to implement them, where indeed, they did so. The thesis argues that these three perspectives together offer valuable insight into understanding the overall course of the Russian revolution and the emergence of the soviet state. They contribute to the western and Russian historiographies on early soviet trade and the economy, while simultaneously engaging with broader scholarship. The thesis not only contributes to the political and ideological histories of the central party leadership, but also to the scholarship on how Russian regions experienced their own revolutions, and the developing relationship between centre and locality in the years after 1917. This study also engages with wider modern history. It places Bolshevik theory and policy within international intellectual trends that sought moral advancement through rational social organisation. The thesis is interested in the perspectives of both the central Bolshevik leadership and of the party and state agents responsible for working directly in the trading sphere. For the former, it relies mainly on published documents such as leaders' collected works, books of decrees, and official transcripts of high-level meetings. For the latter it uses Russian archive materials, especially hitherto unpublished documents from the soviet foreign trade sector. The thesis conducts two case studies of Petrograd party and state apparatuses dedicated to running and regulating overseas commerce in the early 1920s.